Usability evaluation framework for Malaysian hospital / Siti Norsazlina Haron - Haron, Siti Norsazlina (Institute of Graduate Studies, UiTM, 2016)
The main priority of the Malaysian Hospital design quality has been to organise an informational domain for patient-oriented care design that requires a userfriendly environment. Despite the variety of quality design assessment, the usability evaluation has brought a new dimension in tracking the quality in-use by exploring the meaning of users’ experiences. Furthermore, those methods lack the procedures that can effectively identify the needs of users would lead to what of the quality dimension to be considered in its implementation. Therefore, the aim of this research had been to develop a usability evaluation framework, in which the nature of patients and visitors’ experience could affect the quality of Hospital environments. The theoretical part suggested that the experiences of hospital end-users might be understood through their feedback on the status of Hospital environments by extending usability and quality theories. This research adopted nine usability criteria, which were identified from the literature. After synthesising the literature, a usability evaluation framework was developed. In addition, the usability parameters for each usability criteria and the domain of user experience context of-use the Hospital physical environment were investigated. Phenomenological philosophy and qualitative dominant approach with case studies were carried out in three Malaysian public hospitals…